Gamma Knife Radiosurgery in Pediatric Patients: Indications and Evolution over Twenty Years of Experience - Goulenko, Victor; Recker, Matthew J.; Iovoli, Austin J.; Reber, Danielle E.; Madhugiri, Venkatesh S.; Plunkett, Robert J.; Podgorsak, Matthew B.; Prasad, Dheerendra (Indian Journal of Neurosurgery, 2025)
This article aims to summarize 22 years of pediatric experience using three generations of the Gamma Knife and show how technological advances in the machine have led to better safety, patient tolerance, and wide application.A retrospective review of Gamma Knife radiosurgery (GKRS) patients younger than 18 years, treated from 1999 to 2020, was conducted. Data points include primary pathology, age, lesion volume, radiation dose, fixation type, and single session versus hypofractionation. The Gamma Knife models used during this period were the Model 4C, Perfexion, and Icon, and we discuss the evolved planning and treatment delivery options.Fifty-five patients aged 2.8 to 18 years (49% between 15 and 18 years old) underwent 80 treatments: 55% of patients had tumors, and 45% had AVMs. A rigid frame was used for 49 patients; while six were secured with a thermoplastic mask, five patients had single session, with one having multiple treatments and one hypofractionation. In this group, six sessions were under general anesthesia and six with monitored anesthesia care. They presented mean deviation from the post-stereotactic registration baseline of 0.15 mm. The median dose was 20 Gy (8–28 Gy), and the median lesion volume was 1.066 cc (0.081–34.791 cc). No radiation-induced tumors have been detected in the follow-up so far.GKRS is a viable modality for pediatric patients needing intracranial radiation. A variety of tumors, as well as AVMs, can be treated. Some level of anesthesia/sedation is required for most patients. The advent of thermoplastic mask fixation has expanded the use of the Gamma Knife to younger patients.
Keywords: pediatric; neuro-oncology; arteriovenous malformation; Gamma Knife radiosurgery